Effect of cengkeh leaves and kayu manis cortex essential oils blend as anti dental plaque - Ardani, Marisya; Pratiwi, Sylvia Utami Tunjung; Hertiani, Triana (Indonesian Journal of Pharmacy, 2010)
Dental  plaque  is  a  mouth  cavity  health  problem  related  to  microbial biofilm,  where  Streptococcus  mutans is  predominant.  Adding  of  essential  oils blend  in  mouthwash  has  been  reported  to  increase  the  dental  plaque  inhibitory activity.  The  essential  oils  of  clove  leaves  (Syzygium  aromaticum (L.)  Merr.  & Perry) and cinnamon cortex (Cinnamomum burmanniNees ex Bl.), are known as potential  antibacterial  and  antibiofilm  towards  S.  mutans.  This  research  aims were  to  reveal  the  influence  of  blending  the  clove  leaves  and  cinnamon  cortex essential  oils  in  antibacterial  and  anti  biofilm  activity  against  S.  mutans and  to find out the optimum composition. Antibacterial assay was performed in nutrient broth  media,  on  microplate  flat-bottom  polystyrene  96  wells.  Biofilm  formation inhibition  and  degradation  assays  were  done  in  BHI  +  2  %  sucrose  on microplate flexible U-bottom PVC 96 wells. Crystal violet1 % was used to stain the biofilm and Optical Density(OD) was measured at λ 595 nm. Simplex Lattice Design formula  was  used  to  calculate  the  blend  optimum  composition.  TLCbioautography and GC-MS assays were done to revealthe active substances. As conclusion,  it  was  proven  that  blending  the  clove  leaves  and  cinnamon  cortex essential  oils  increased  the  antibacterial  and  biofilm  degradation  potency,  but reduced  the  biofilm  formation  inhibitory effect against  S.  mutans. The  optimum composition  of  the  essential  oils  blend  was  27:73  (% v/v).  From  our  results  we suggest  that  the  clove  leaves  and  cinnamon  cortex  essential  oil  blend  used  in this study be developed as anti dental plaque.Key words : clove leaves, cinnamon cortex, essential oils blend, Streptococcus mutans